Mutation Induced Enhanced Production of Bioactive Metabolites by a Mutant Strain of Marine Streptomyces rochei (Isolate No.10) - Gopi Reddy, N.; Ramakrishna, D.P.N.; Rajagopal, S.V. (Asian Journal of Chemistry, 2011)
The selection of spontaneous and induced mutants in Streptomyces might generate enhanced producers of bioactive metabolites. In the present, investigation to enhance the production of biomedically important bioactive metabolites by subjecting the indigenous bioactive metabolites producing strain of Streptomyces rochei to improvement by natural selection and random mutagenesis UV and N-nitroso guanidine (NTG). The isolation of mutants and their antimicrobial activity of the selected mutants were described. The best natural selectant GRRNS3 showed 110 % higher antimicrobial activity than the wild strain. The bioactive metabolites yield of the best UV mutant GRRUV6 was 118 % higher than the parent strain (GRRNS3) and 129 % higher than the wild strain. The bioactive metabolites yield of the best NTG mutant GRRNTG8 was 111 % higher than the parent strain (GRRUV6) and 143 % higher than the wild strain. The results indicate that UV and N-nitroso guanidine were effective mutagenic agents for strain improvement of wild strain Streptomyces rochei for enhanced bioactive metabolites productivity.